Legal Analysis Land Parcel Sale and Purchase Agreement Entered Into by Dewe Land Parcel Developer in Kudus Regency - Mohammad Yusrul Hana; Agus Ariadi (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the validity and legal certainty of the sale and purchase agreement of land plots conducted by developer Kavling Dewe in Kudus Regency, and to identify clauses that have the potential to harm consumers (adverse clauses). The type of research used is normative juridical with statutory and conceptual approaches. The data used is secondary data sourced from primary, secondary, and tertiary legal materials. The results show that substantively, the sale and purchase agreement made by developer Kavling Dewe has fulfilled the requirements for a valid agreement as regulated in Article 1320 of the Indonesian Civil Code (KUHPerdata). However, in practice, several clauses were found to be entirely dominated by the developer, such as clauses regarding late payment, force majeure, and dispute resolution which tend to burden the consumer and are unbalanced. These clauses have the potential to contradict the principle of good faith and the principle of balance in contract law, and violate the provisions of Law Number 8 of 1999 concerning Consumer Protection. Stricter supervision from the Financial Services Authority (OJK) and the Consumer Dispute Settlement Agency (BPSK) is needed to ensure balanced legal protection for the parties.